Axially Substituted Silicon Phthalocyanine Payloads for Antibody–Drug Conjugates - Takahashi, Kazuki; Sugiyama, Akira; Ohkubo, Kei; Tatsumi, Toshifumi; Kodama, Tatsuhiko; Yamatsugu, Kenzo; Kanai, Motomu (Synlett, 2021)
IR700, a silicon phthalocyanine (SiPc) photosensitizer, is an antibody–drug conjugate payload used clinically. It is, however, the sole SiPc payload to date, possibly due to the difficulty of its synthesis, resulting from its asymmetric phthalocyanine skeleton. Here, we report a new axially substituted SiPc payload that is more easily synthesized. Trastuzumab conjugated with the SiPc showed light- and antigen-dependent cytotoxicity in HER2-overexpressing cancer cell lines.
Keywords: phthalocyanines; antibody–drug conjugates; photodynamic therapy; cancer; medicinal chemistry